Lung Cancer incidence in both sexes across global areas: data from 1978 to 2017 and predictions up to 2035 - Dong-Ning Lu; Yan Jiang; Wan-Chen Zhang; Rong-Kang Du; Ao Zeng; Yi-Mu Wu; Xiao Zhou (BMC Pulmonary Medicine)
Abstract Background and aim Lung cancer (LC) is one of the most prevalent and fatal malignancies worldwide. With the progress of society, the pathogenic factors, medical diagnosis, and environmental health policies of lung cancer have all changed. Therefore, predicting the incidence trend of LC is of significance for people to understand the future burden of LC.In this study, we aimed to analyze temporal trends in LC incidence across 45 areas from 1978 to 2017, investigate regional and demographic patterns of LC incidence, and predict trends from 2018 to 2035. Methods Data on annual LC cases and population statistics, stratified by age and sex, were collected from 111 cancer registries in 45 areas across five continents using the Cancer Incidence in Five Continents Plus database. From 1978 to 2017, age-standardized rates (ASRs) per 100,000 individuals were calculated for both sexes and different age groups. A Bayesian age-period-conhort (BAPC) model was applied to forecast ASRs until 2035. Results From 1978 to 2017, LC ASRs decreased in most areas for men (32/45 areas) but increased for women (37/45 areas), and mainly due to the rising incidence rate among elderly women (> 60 years old). Among men, the country with the largest increase was Cyprus (+ 71.95%), and the largest decrease was Costa Rica (-64%). Among women, France saw the greatest increase (+ 515.15%) while Kuwait had the least (-72.85%). In addition, the LC ASR in high-income areas is higher than that in middle - and low-income areas. However, projections from 2018 to 2035 suggested that only 8 of 45 areas will witness increasing LC ASRs for men, whereas 18 areas will experience ASR increases for women. Conclusion Overall, global LC incidence is gradually declining. However, considerable disparities exist across areas, sexes, and developmental stages. Therefore, understanding area-specific trends, customizing control measures to local contexts, and conducting screening and early interventions in high-incidence areas and populations are central to overcoming these differences. Clinical trial number Not applicable.